Dealing with interethnic conflicts by civil society in Serbia: Activities and discourse - Nikolić-Ristanović Vesna (Temida, 2013)
This paper aims to present a cross-section of the results of the research “Fostering victim-oriented dialogue in a multiethnic society”, conducted by the Victimology Society of Serbia during the first and the beginning of the second year of the implementation of the project “ALTERNATIVE - Developing alternative understandings of security and justice through restorative justice approaches in intercultural settings within democratic societies.” The research focuses on inter-ethnic conflicts that occurred from the 1990s onwards among the civil society organizations in Serbia. The results relating to the activities of these organizations as well as to the discourse, specifically the way they speak in public about inter-ethnic conflicts, are presented. Special attention is paid to identifying activities that have elements of restorative justice, as well as to an assessment of the potential that existing restorative activities have for solving problems in inter-ethnic relations, and building peace and security for the citizens of Serbia in general, particularly for those living in the multinational regions near borders with other countries of the former Yugoslavia. [Ovaj rad nastao je kao rezultat rada na projektu koji je dobio finansijsku podršku EU u okviru Sedmog okvirnog programa Evropske komisije za istraživanja i tehnološki razvoj (FP7-SEC-2011-1), ugovor broj 285368]